Pengembangan E-Modul Interaktif Berbasis Android Dalam Mata Kuliah Bunpou I - Noverisa, Eva Jeniar (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
The purpose of this study is to produce an interactive prototype of an Android-based e-module and to find out the opinions of experts and students regarding the prototype. This multi-year research was carried out to answer the needs of students in obtaining and accessing learning material that is easier, cheaper, and not only has practical value but also flexibility value. The research can be a reference in developing 21st Century skills-based Japanese learning media. The first year of research uses the Research and Development (R&D) method with a descriptive-qualitative approach. The research took place from March to December 2021. Research’s sample was 21 students of Bunpou I, 2 media experts and 2 content experts. The results showed that this prototype got a score of 3.52 with category ‘very good’ for the content. It got 3.1 score for media display which is in category ‘good’. The results also showed that there are several notes for improving e-modules such as adding more interesting illustrations, improving forms and evaluation scores, improving user interfaces, adding sample sentences to reducing dependence on hyperlinks in the network. Most of the respondents liked this e-module and found it helpful in understanding basic level of Japanese easily. Bright color display makes learning less boring. The existence of videos, and exercises with a score system can also help increase learning motivation.